Considerações sobre os indicadores de resultado de políticas de assistência social em municípios de Mato Grosso - Bombassaro, Loide Santana Pessoa (2014)
This master’s thesis is concerned with outcome indicators for analysis, monitoring and evaluation of social assistance policies in Municipalities of State of Mato Grosso. The aim of this thesis is to analyze outcome indicators of social assistance policies in Municipalities of State of Mato Grosso. The research was conducted under the theoretical framework of dialectical historical materialism, searching to understand the reality resulting from the dynamics among the main systems that affect the social relationships: the economic, political and the social systems. That dynamics happen by means of a contradictory process and in constant transformation; The research used the qualitative methodological approach with documentary data collection, mainly examining social assistance plans, strategic plans and documents of public budget and planning: long term plans, law of budgetary directives and budgetary law of municipalities; with participant observation of the process of changing of plans and of creation of objectives, goals and indicators. The results show that the indicators used in the strategic plans, in the documents of planning and budget do not provide ways to measure the outcome of social assistance policy. Keywords: